2012
DOI: 10.1111/j.1758-5872.2012.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic overlap of depressive, anxiety, stress and somatoform disorders in primary care

Abstract: Introduction The aim of the present study was to determine the prevalence of somatization, anxiety, depression and stress in a primary care population, explore their association to psychosocial stressors and determine the diagnostic overlap of these four mental disorders. Methods This is a prospective cross‐sectional study. A representative sample of 2,150 patients was approached, of whom 1,762 patients agreed to participate and responded to the questionnaire (81.9%). Anxiety was assessed with the Generalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 20 publications
2
37
0
2
Order By: Relevance
“…Also, a recent study observed a high rate of comorbidity of somatization, depression, anxiety, and stress in the studied population and indicated a strong association between these psychological disorders in patients 6. Considering the results of these two studies, the authors understood the importance of focusing on LBP issues in the general population of Qatar and exploring the potential psychological differences between patients with and without LBP.…”
Section: Introductionmentioning
confidence: 92%
“…Also, a recent study observed a high rate of comorbidity of somatization, depression, anxiety, and stress in the studied population and indicated a strong association between these psychological disorders in patients 6. Considering the results of these two studies, the authors understood the importance of focusing on LBP issues in the general population of Qatar and exploring the potential psychological differences between patients with and without LBP.…”
Section: Introductionmentioning
confidence: 92%
“…disorders in patients (3). In a recent study, they stated that psychological distress such as anxiety, depression, and somatization were more prevalent in LBP patients compared to patients without LBP (4).…”
mentioning
confidence: 99%
“…These data indicate that approximately 1 out of 3 patients in the PC setting suffers from some type of mental disorder. In addition, comorbidity in these patients is high [4-6] and closely associated with poor quality of life [7], substance misuse, disability, and high health and social costs that rise in parallel with the increase in the number of comorbid disorders [8]. …”
Section: Introductionmentioning
confidence: 99%